Increased risk of cardiac ischaemia in a pan-European cohort of 36 205 childhood cancer survivors: a PanCareSurFup study. Issue 1 (21st August 2020) - Feijen, Elizabeth Arnoldina Maria; van Dalen, Elvira C; van der Pal, Heleen J H; Reulen, Raoul C; Winter, David L; Kuehni, Claudia E; Morsellino, Vera; Alessi, Daniela; Allodji, Rodrigue S; Byrne, Julliana; Bardi, Edit; Jakab, Zsuzsanna; et al.
Abstract : Objective: In this report, we determine the cumulative incidence of symptomatic cardiac ischaemia and its risk factors among European 5-year childhood cancer survivors (CCS) participating in the PanCareSurFup study. Methods: Eight data providers (France, Hungary, Italy (two cohorts), the Netherlands, Slovenia, Switzerland and the UK) participating in PanCareSurFup ascertained and validated symptomatic cardiac events among their 36 205 eligible CCS. Data on symptomatic cardiac ischaemia were graded according to the Criteria for Adverse Events V.3.0 (grade 3–5). We calculated cumulative incidences, both overall and for different subgroups based on treatment and malignancy, and used multivariable Cox regression to analyse risk factors. Results: Overall, 302 out of the 36 205 CCS developed symptomatic cardiac ischaemia during follow-up (median follow-up time after primary cancer diagnosis: 23.0 years). The cumulative incidence by age 60 was 5.4% (95% CI 4.6% to 6.2%). Men (7.1% (95% CI 5.8 to 8.4)) had higher rates than women (3.4% (95% CI 2.4 to 4.4)) (p<0.0001). Of importance is that a significant number of patients (41/302) were affected as teens or young adults (14–30 years). Treatment with radiotherapy/chemotherapy conferred twofold risk (95% CI 1.5 to 3.0) and cases in these patients appeared earlier than in CCS without treatment/surgery only (15% vs 3% prior to age 30 years, respectively (p=0.04)). Conclusions: In this very large European childhood cancer cohort, we found that by age 60 years, 1 in 18 CCS will develop a severe, life-threatening or fatal cardiac ischaemia, especially in lymphoma survivors and CCS treated with radiotherapy and chemotherapy increases the risk significantly.